Internal tide generation in nonuniformly stratified deep oceans. Issue 3 (17th March 2014) - Paoletti, M. S.; Drake, Matthew; Swinney, Harry L.
Abstract We present numerical and experimental studies of the conversion of tidal motions of an exponentially stratified fluid over two‐dimensional knife edge, Gaussian, and complex bottom topography to radiated internal waves in a model of the deep ocean. We compare the radiated internal wave power for cases of strong stratification, where the buoyancy frequency profile N(z) (proportional to the square root of the density gradient) is much larger than the tidal frequency ω, to the power radiated for weak stratifications. We consider particularly internal wave generation for topography below a turning depth ztd, where <alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgg5508wn5b" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />N(ztd )=ω</alternatives>; for <alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgg5508wn80" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />z<ztd</alternatives>, internal waves are evanescent. We find that topography below a turning depth does generate internal waves that propagate for <alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgg5508wn9j" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />z>ztd</alternatives>, although the radiated power in these waves is much weaker than in cases without turning depths. The radiated power is predicted well by prior analytical theory if the nonuniform stratification is averaged over depths spanning from the bottom boundary up to an effective height zeff. In the absence of a turning depth, we find zeff is approximately equal to the height of the topography, indicating that only the stratification for depths spanned by the topography is relevant. However, in the presence of a turning depth, the vertical scale of the internal tide becomes larger, and zeff increases approximately linearly with the turning depth height toward values comparable to the total fluid depth.